2021
DOI: 10.1002/lsm.23391
|View full text |Cite
|
Sign up to set email alerts
|

Incident Fluence Analysis for 755‐nm Picosecond Laser Treatment of Pigmented Skin Lesions Based on Threshold Fluences for Melanosome Disruption

Abstract: Background and Objectives In this study, the threshold fluences for disrupting the melanosomes for pigmented skin lesion treatment were determined using a 755‐nm picosecond laser for clinical use. Based on the melanosome disruption thresholds, incident fluences corresponding to the target lesion depths were evaluated in silico for different laser spot sizes. Study Design/Materials and Methods Melanosome samples were isolated from porcine eyes as alternative samples for human cutaneous melanosomes. The isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…Lately, Yu et al investigated the threshold fluences for the melanosomes using the 755‐nm alexandrite picosecond laser and demonstrated that the threshold fluence at a pulse width of 750 ps is 2.49 J/cm 2 . The incident fluence may differ according to the depth of the melanosomes distributed in the skin tissue, and to destroy more deeply located melanosomes, larger spot sizes are preferred 8 . In light of these research results, parameters including a pulse width of 750 ps, a frequency of 1 Hz, a spot size of 3.2 mm, and an energy density of 2.49 J/cm 2 were used for this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, Yu et al investigated the threshold fluences for the melanosomes using the 755‐nm alexandrite picosecond laser and demonstrated that the threshold fluence at a pulse width of 750 ps is 2.49 J/cm 2 . The incident fluence may differ according to the depth of the melanosomes distributed in the skin tissue, and to destroy more deeply located melanosomes, larger spot sizes are preferred 8 . In light of these research results, parameters including a pulse width of 750 ps, a frequency of 1 Hz, a spot size of 3.2 mm, and an energy density of 2.49 J/cm 2 were used for this case.…”
Section: Discussionmentioning
confidence: 99%
“…The incident fluence may differ according to the depth of the melanosomes distributed in the skin tissue, and to destroy more deeply located melanosomes, larger spot sizes are preferred. 8 In light of these research results, parameters including a pulse width of 750 ps, a frequency of 1 Hz, a spot size of 3.2 mm, and an energy density of 2.49 J/cm 2 were used for this case. Seven days after the initial treatment, the local lesions had scabbed, and the scab fell off without scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…52 Our previous study also indicated that a lower fluence of a picosecond laser pulse could produce treatment effects. 7 These studies suggest that immediate whitening may not be always necessary. Validation of the numerical results will lead to an improved selection of laser irradiation parameters for the treatment of epidermal pigmented lesions.…”
Section: Studymentioning
confidence: 99%
“…Compared with laparotomy and laparoscopic access, endoscopic access minimizes the number of incisions and sutures 7 . Furthermore, laser treatment is contactless, has high selectivity and high resolution, and has the possibility of automation based on robotic techniques 8 and numerical simulations 9 11 . Thus, endoscopic laser treatment offers minimally invasive treatment, short surgery time, and optimal precision 7 .…”
Section: Introductionmentioning
confidence: 99%